Nursing diagnoses in newborns in a maternity in a Northeast brazilian city (Research, Society and Development, 2020)
Objective: To identify the prevalence of nursing diagnoses and their defining characteristics in newborns based on clinical indicators of human responses identified. Methodology: A descriptive and cross-sectional study was carried out with 45 newborns in the period from December 2018 to February 2019, with data collected by means of physical examination and survey of the nursing history. For the appointment of diagnoses, the NANDA-I Taxonomy II was used. Results: The following diagnoses were identified: Risk of infection (80%), Risk of delayed development (55.5%), Ineffective breastfeeding (28.8%), Ineffective respiratory pattern (17.7%), Risk of decreased cardiac output (4.4%). Final thoughts: The research revealed five nursing diagnoses with their defining characteristics and related factors or risk factors in newborns. The identified diagnoses in most of the newborns were related to the risk of infection and risk of delayed development. In this way, the importance of critical and reflective thinking is emphasized, based on scientific evidence on the part of the nurse to ensure a qualified assistance using the systematization of nursing assistance.